2020
DOI: 10.1186/s12943-020-01272-9
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA circ-ERBIN promotes growth and metastasis of colorectal cancer by miR-125a-5p and miR-138-5p/4EBP-1 mediated cap-independent HIF-1α translation

Abstract: Background Circular RNA (circRNAs) and hypoxia have been found to play the key roles in the pathogenesis and progression of cancer including colorectal cancer (CRC). However, the expressions and functions of the specific circRNAs in regulating hypoxia-involved CRC metastasis, and the circRNAs that are relevant to regulate HIF-1α levels in CRC remain elusive. Methods qRT-PCR was used to detect the expression of circRNAs and mRNA in CRC cells and tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 40 publications
1
103
0
Order By: Relevance
“…A number of studies have found that miR-138-5p exerted a tumor-suppression role in CRC. 25–27 Xu et al indicated that miR-138-5p inhibited cell migration and enhanced chemoresistance in CRC cells by NFIB-Snail1 axis. 26 In our research, miR-138-5p was downregulated in CRC tissues and cells and was negatively correlated with circ_0006174 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that miR-138-5p exerted a tumor-suppression role in CRC. 25–27 Xu et al indicated that miR-138-5p inhibited cell migration and enhanced chemoresistance in CRC cells by NFIB-Snail1 axis. 26 In our research, miR-138-5p was downregulated in CRC tissues and cells and was negatively correlated with circ_0006174 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The number of microvessels were greatly increased in circERBIN overexpression tumors as analyzed by staining CD31, a sensitive vascular marker to evaluate tumor angiogenesis. They further confirmed that circERBIN promoted tumor angiogenesis by increasing a cap-independent protein translation of HIF-1α through miR-125a5p/miR-138-5p/4EBP-1 signaling ( 148 ).…”
Section: Roles Of Circrnas In Human Cancermentioning
confidence: 70%
“…It has also been reported that circRNAs can be spliced with linear RNA, thereby smoothly "capturing" mRNA and then regulating the life process [42]; circRNAs can also interact with RNA polymerase II (Pol II), thereby promoting the transcription of parent genes [31]. Some circRNAs can regulate the normal physiological activities of biological individuals by participating in the synthesis of body proteins [43,44]. For example, circ-Amotl1 physically binds to both 3-phosphoinositidedependent protein kinase 1 (PDK1) and protein kinase B (AKT), facilitating the cardioprotective nuclear translocation of pAKT [45].…”
Section: Characteristics Of Circrnas and Their Biological Functionsmentioning
confidence: 99%
“…For example, circ-Amotl1 physically binds to both 3-phosphoinositidedependent protein kinase 1 (PDK1) and protein kinase B (AKT), facilitating the cardioprotective nuclear translocation of pAKT [45]. Very few circRNAs can be used as translation templates to promote translation [44]. Recently, some studies have shown that circRNAs can also be used as biomarker molecules [46,47] and are currently used as markers for the diagnosis of related diseases [45].…”
Section: Characteristics Of Circrnas and Their Biological Functionsmentioning
confidence: 99%